Fresno County Bar Association's Barristers Benefit Ball at the Fresno Metropolitan Museum - Watkins, Howard::::::::: (1988)
Seated: Stephanie Oliver, Mary Jo Keyes, Robert Koligian, and Sheila Smith; Standing: Robert Oliver, Hon. Dwayne Keyes, Mary Lee Levy, and Herbert Levy